(untitled) (Contemporary Journal of Social Science Review, 2025)
The core objective of this study is to explore the key factors associated with land mafias and corruption within various government departments and agencies that contribute to the rising number of land litigation and land dispute cases in Pakistan. A qualitative approach was employed, utilizing structured interviews and focus group discussions to collect data from land revenue officers and lawyers actively involved in land litigation processes. Based on the data analysis, the study identified fifteen critical themes that significantly contribute to land disputes and litigation. These include: forgery of land documents, organized land grabbing, bribery in land registration and transfer, collusion with government officials, fraudulent housing schemes, creation of fake land titles, political and legal influence, obstruction of land reforms, encroachment on public and communal lands, manipulation of the legal system, intimidation and coercion, illegal land subdivision, unlawful occupation of agricultural land, eviction of legitimate landowners, and corruption in land surveys and demarcation processes. The findings of this study are intended to empower policymakers and stakeholders to formulate targeted policies, rules, and regulations based on these themes, thereby helping to reduce land litigation cases linked to land mafias and institutional corruption in Pakistan.